Teacher Strategies and Students’ Engagement in TEFL Based on Killen’s Theory at SMP Negeri B. Srikaton - Dafa Alya Nabilla; Ardayati Ardayati; Maria Ramasari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The objective of the research was to find out the teacher strategies in TEFL based on Killen’s theory at SMP Negeri B. Srikaton and to describe the students' engagement in learning English at SMP Negeri B. Srikaton. There were two research questions in this research, what are the teacher strategies in TEFL based on Killen’s theory at SMP Negeri B. Srikaton? and how are the students' engagement in learning English at SMP Negeri B. Srikaton? The setting of this research were SMP Negeri B. Srikaton. The qualitative approach in descriptive qualitative research design was used in this research because the data was in the form of words rather than the number. The data were collected by means of the observation, interviews, and documentation. Then the data were analyzed by table observation cheklist and analyzing. The result of this research show, there were found 8 teachers strategies and students Engagement. First 3 strategies and students engagement, and second material 7 teachers strategies. Teacher used strategies and the students active in learning process. Therefore, teachers use different learning strategies in each material so that students are engage and active in the learning process.